Catalytically Active Nanocomposites Based on Palladium and Platinum Nanoparticles in Poly(2‐vinylpyridine) Brushes. Issue 20 (25th July 2013) - Koenig, Meike; Simon, Frank; Formanek, Petr; Müller, Martin; Gupta, Smrati; Stamm, Manfred; Uhlmann, Petra
<x xml:space="preserve">Abstract</x> Novel catalytically active nanocomposite surfaces are fabricated by in situ synthesis of palladium or platinum nanoparticles inside poly(2‐vinylpyridine) (P2VP) brushes, used as a nano‐reactor. Focusing on the revelation of the interaction of the metal species with P2VP, the immobilization is investigated by X‐ray photoelectron spectroscopy (XPS), attenuated total reflection Fourier transform IR (ATR‐FTIR) spectroscopy, atomic force microscopy (AFM), as well as scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Homogeneous distribution of nanoparticles is achieved. The mechanism of nanoparticle formation is investigated by studying the influence of particular reaction parameters and the catalytic activity of the nanocomposites is confirmed using a model reaction. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>